Space Race Between China and India to Win Hegemony - Antonia Rahayu Rosaria Wibowo (Jurnal Ilmu Sosial, 2022)
Space race refers to the race to master space technology. This activity began in the Cold War Era when the United States of America and the Soviet Union raced to explore outer space in the 1950s. The race continued and at the end of the 1960s other countries followed to conduct space activities by launching rocket and satellite. China and India are two countries which have advance technological development and those countries also compete in mastering space technology. Besides having rapid capability to master space technology, China and India also show the same interest to win global authority. This research is important because studying the use of space technology to win hegemony is a new topic. This research attempts to answer a research problem related to the efforts conducted by China and India to win hegemony through space race. This research aims to give new insight on the use of space technology to win hegemony. It was qualitative research which used descriptive method and library research technique to collect secondary data about China and India’s space activities and also the space race between them from books, scientific journals, and other relevant sources. The analysis results show that China and India use their space capabilities to win hegemony.